2013
DOI: 10.21273/jashs.138.4.243
|View full text |Cite
|
Sign up to set email alerts
|

Four Hypotheses to Explain Axillary Budbreak after Removal of Flower Shoots in a Cut-rose Crop

Abstract: When flower-bearing shoots in cut-rose (Rosa ×hybrida) are harvested (removed), a varying number of repressed axillary buds on the shoot remainder start to grow into new shoots (budbreak). Besides removing within-shoot correlative inhibition, it is hypothesized that shoot removal leads to 1) increased light intensity lower in the crop canopy; 2) changes in the light spectrum (particularly red:far-red ratio); and 3) changed source:sink ratio (i.e., t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…On the basal part of the shoot that is left (the shoot remainder), axillary buds break and develop into the next harvestable flower shoots. A previous study (Wubs et al, 2013) indicated that the degree of budbreak on shoot remainders positively responded to more light in combination with higher red:far-red ratio received by the buds, but effects of light intensity and light spectrum could not be separated. The experiments in this study were set up to disentangle the effects of light intensity and red:far-red ratio reaching the axillary buds in a rose crop, trying to determine whether one or the other is more important for triggering axillary budbreak of a crop or that both are equally important.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…On the basal part of the shoot that is left (the shoot remainder), axillary buds break and develop into the next harvestable flower shoots. A previous study (Wubs et al, 2013) indicated that the degree of budbreak on shoot remainders positively responded to more light in combination with higher red:far-red ratio received by the buds, but effects of light intensity and light spectrum could not be separated. The experiments in this study were set up to disentangle the effects of light intensity and red:far-red ratio reaching the axillary buds in a rose crop, trying to determine whether one or the other is more important for triggering axillary budbreak of a crop or that both are equally important.…”
Section: Discussionmentioning
confidence: 86%
“…However, the number of broken buds is variable: a plant has several axillary buds, which potentially form a shoot, but not all of them do. As discussed by Wubs et al (2013), shoot removal (harvest) not only removes apical dominance and correlative inhibition, but also leads to 1) increased light intensity reaching the axillary bud; and 2) changed spectrum of light reaching the bud (particularly a higher red:far-red ratio); and 3) changed source:sink ratio (i.e., the ratio between supply and demand of assimilates). Furthermore, the degree of budbreak on a shoot remainder is also influenced by the correlative inhibition exerted by other shoots on the plant (Wubs et al, 2013;Zieslin and Halevy, 1976).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This may affect compensatory responses such as leaf area production due to changes in source-sink relations, as stem can be a storage organ for assimilates. Branch pruning also stimulates axillary bud break because of the removal of correlative inhibition and the increase of light intensity at the positions of axillary buds due to branch removal (Wubs et al, 2013). Shoot bending is normally applied in some woody species crops (e.g., rose) and fruit trees (e.g., apple and pear) (Ito et al, 1999;Han et al, 2007;Liu & Chang, 2011;Lopez et al, 2014).…”
Section: Photosynthesis Responses To Changes In Plant Structurementioning
confidence: 99%